2011
DOI: 10.1136/ard.2011.151092
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing surveillance of tocilizumab for rheumatoid arthritis in Japan: interim analysis of 3881 patients

Abstract: ObjectiveAn interim analysis of an all-patient postmarketing surveillance programme in Japan to investigate the safety of tocilizumab for the treatment of rheumatoid arthritis (RA) in the real world.MethodsThis analysis included 3881 patients. Patients received 8 mg/kg of tocilizumab every 4 weeks, and were observed for 28 weeks. Data on baseline characteristics and adverse events (AE) were collected.ResultsTotal and serious AE were reported as 167 and 27 events/100 patient-years, respectively. The most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(115 citation statements)
references
References 18 publications
10
100
1
4
Order By: Relevance
“…The safety and effectiveness profiles of TCZ reported here are consistent with the results of the interim analysis of this study 1 . The most common AE and SAE reported in this analysis were infections.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The safety and effectiveness profiles of TCZ reported here are consistent with the results of the interim analysis of this study 1 . The most common AE and SAE reported in this analysis were infections.…”
Section: Discussionsupporting
confidence: 80%
“…Multivariate logistic regression analysis identified the following risk factors for serious infection: age ≥ 65 years, longer disease duration (≥ 10 yrs), previous or concurrent respiratory disease, and mean concomitant corticosteroid dose > 5 mg/day (prednisolone equivalent). The risk factors for serious infection identified in our study are similar to the findings reported from the all-patient PMS conducted for infliximab, etanercept, and adalimumab in Japan 1,13,14,15 . Patients with 3 or more of these risk factors had a cumulative incidence of serious infection about 10 times that of patients with no risk factors.…”
Section: Rheumatologysupporting
confidence: 79%
See 2 more Smart Citations
“…Expectations related to the usefulness of tocilizumab are high. However, an all-case post-marketing survey for tocilizumab (Koike et al, 2010) found that, among patients with progressive renal disorders with multiple organ failure in whom tocilizumab was used for life-saving purposes, complications such as infections and deaths were reported. Therefore, considerable caution is required when tocilizumab is used.…”
Section: A B C Dmentioning
confidence: 99%